Factors associated with HIV viral load suppression on antiretroviral therapy in Vietnam - Suresh Rangarajan; Donn J. Colby; Le Truong Giang; Duc Duong Bui; Huu Hung Nguyen; Plui Broh Tou; Tran Tri Danh; Ngoc Bao Chau Tran; Duc Anh Nguyen; Bao Tram Hoang Nguyen; Vu Tuyet Nga Doan; Nhat Quang Nguyen; et al. (Elsevier, 2016)
Background: Limited data are available on HIV viral suppression rates among men and women on antiretroviral therapy (ART) and factors associated with HIV RNA viral load (VL) suppression in Vietnam. Methods: We conducted a cross-sectional survey of 1255 adult patients on ART for at least 1 year across four provinces in Vietnam. Data collection included a standardised questionnaire, routine laboratory testing, and an HIV VL assay. Bivariate and logistic multivariate analyses were conducted to assess viral suppression rates and factors associated with unsuppressed HIV VL. Results: The median age was 34.5 years and the median time on ART was 46 months. Gender was 66% male (n=828) and 34% female (n=427). HIV viral suppression below 1000 copies/mL was 93%. Viral suppression among woman was not significantly different than among men (93.7% vs92.9%; P=0.59). On multivariate analysis, unsuppressed HIV VL was independently associated with lower CD4 cell count, social isolation, high stigma, not receiving a single-tablet daily regimen, multiple late appointments in past year, and immunological failure. Conclusion: On-treatment viral load suppression rates in Vietnam are high and already exceed the UNAIDS 90% target for viral suppression on ART. Gender does not impact viral suppression rates of patients on ART in Vietnam. Access to routine viral load testing should be improved, adherence monitoring and counselling streamlined, and ART regimens simplified to maintain viral suppression rates, as more people start ART. Psychological and social factors are also associated with unsuppressed HIV VL, necessitating treatment support interventions to address social isolation and stigma among people living with HIV in Vietnam.